2007
DOI: 10.1373/clinchem.2006.074930
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of Circulating Carotenoid Concentrations with Several Markers of Inflammation, Oxidative Stress, and Endothelial Dysfunction: The Coronary Artery Risk Development in Young Adults (CARDIA)/Young Adult Longitudinal Trends in Antioxidants (YALTA) Study

Abstract: Background: Serum carotenoid concentrations relate inversely to cardiovascular disease incidence. To clarify the effect of carotenoids on atherosclerotic risk factors, we examined the association of circulating carotenoids with inflammation, oxidative stress, endothelial dysfunction, and smoking. Methods: Black and white men and women in the Coronary Artery Risk Development in Young Adults study, ages 18 to 30 years at recruitment (1985-1986) from 4 US cities, were investigated over 15 years. We included 2048 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
126
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(147 citation statements)
references
References 47 publications
17
126
0
4
Order By: Relevance
“…Carotenoids have been shown to inhibit proliferation of transformed cells (45,46), to reduce inflammatory response (31), and, indirectly through conversion to retinol, to induce epithelial cell differentiation (47,48). In addition, although greater intake of fruits and vegetables is consistently associated with higher plasma carotenoid concentrations (49)(50)(51) and has been shown in the parent WHEL cohort (24), it may be the combination of carotenoids and other bioactive food components and nutrients found in these plant foods that affords protection.…”
Section: Discussionmentioning
confidence: 99%
“…Carotenoids have been shown to inhibit proliferation of transformed cells (45,46), to reduce inflammatory response (31), and, indirectly through conversion to retinol, to induce epithelial cell differentiation (47,48). In addition, although greater intake of fruits and vegetables is consistently associated with higher plasma carotenoid concentrations (49)(50)(51) and has been shown in the parent WHEL cohort (24), it may be the combination of carotenoids and other bioactive food components and nutrients found in these plant foods that affords protection.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that people who consumed avocado regularly tended to have a sufficient nutrient supply of dietary fibre, vitamin K, vitamin E, potassium, magnesium, as well as vitamin B complex [14]. These nutrients provide a wide range of potential health benefits such as preventing hypercholesterolemia [15], vascular damage [16], and reduce the risk of atherosclerosis [17]. The consumption of avocado has been investigated to have positive effects on lipid profiles [18] by increasing HDL cholesterol levels, reducing lipid serum peroxidation, and promoting cardiovascular health [19].…”
Section: Introductionmentioning
confidence: 99%
“…Plant-based fat sources have great potentials to be used as a replacement for dairy-based fat sources in the ice cream formulation. Furthermore, plant-based sources are generally less expensive compared to dairy fat [21] and provide advantages towards health [15], [16], [17], [18], [19]. The objective of this study was to analyze the physicochemical, rheological and sensorial properties of ice cream that have been substituted with different concentrations of avocado paste.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, carotenoids also exert positive influences on the immune response which may be, at least in part, mediated by their antioxidant effects (14). Both in population-based studies and in studies of coronary patients, inverse associations between circulating carotenoids and markers of systemic inflammation have been reported (15)(16)(17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%